The Influence Of Profitability And Solvency On The Value Of Financial Companies Listed On The Indonesian Sharia Stock Index In 2018-2023 - Sahri Muliani; Munawarah (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study aims to analyze the effect of profitability and solvency on firm value with firm size as an intervening variable in financial sector companies listed on the Indonesian Sharia Stock Index (ISSI) during the period 2018–2023. The type of research used is field research with a quantitative research method. The sample was determined using a saturated sampling method, which involves including the entire population in the sample. Hypothesis testing was conducted using the Smart-PLS application. The results of the study indicate that profitability does not have a direct effect on firm value but does have an indirect effect through firm size. Meanwhile, solvency has a direct effect on firm value but does not have an effect when mediated through firm size. These findings suggest that firm size plays an important role as a link between financial performance and perceived value in the eyes of investors. Overall, this study emphasizes the importance of integrated financial management in shaping growth strategies and sustainably enhancing company value.